Wage Returns to Mid-Career Investments in Job Training through Employer-Supported Course Enrollment: Evidence for Canada - Wen Ci; Jose C. Galdo; Marcel Voia; Christopher Worswick (Institute for the Study of Labor (IZA), 2015)
Using longitudinal data for Canada, we analyze the incidence and wage returns to employer supported course enrollment for men and women. Availability of confidential data, along with a relatively rich set of observable covariates, lead us to the estimation of difference-in-differences matching models of the effect of employer supported course enrolment on wages. The estimated average treatment effects on the treated range from 5.5 to 7.2 percent for men and 7.1 to 9.0 for women. While high-skilled workers show disproportionally higher rates of participation in employer-supported training, we observe no wage premiums for these types of workers. Statistically significant positive wage returns are found, on the other hand, for low-skilled workers.
Keywords: C14; I20; J24; J31; M53; 330; return to adult training; employer supported course enrollment; difference-in-differences model; propensity score matching; Canada